International review of research in developmental disabilities. - Hatton, Deborah Dominey (International review of research in developmental disabilities, 2014)
International Review of Research in Developmental Disabilities is an ongoing scholarly look at research into the causes, effects, classification systems, and syndromes of developmental disabilities. Contributors come from wide-ranging perspectives, including genetics, psychology, education, and other health and behavioral sciences. The current volume, number 46, addresses current issues in the education of students with visual impairments. Topics covered include the expanded core curriculum for students with visual impairment; assistive technology; Braille reading comprehension; communication development; orientation and mobility issues, and more.